S Studi Analisis Waktu Proyek Pembangunan Gedung Kementerian Koordinator 2 di IKN Menggunakan Program Evaluation and Review Technique - Kaligis, Eunike Imania; Rangkang, Jeanely; Tombeg, Beldie Aryona (Jurnal Teknik Sipil Terapan (JTST), 2025)
Accurate scheduling of implementation time is a crucial aspect of construction project management, especially for large-scale office building projects. This study aims to analyze the estimated project completion time using the Program Evaluation and Review Technique (PERT) method and to compare it with the actual project duration based on S-Curve data. The PERT method is used to calculate the average estimated time (te) for each project activity by considering optimistic, most likely, and pessimistic time estimates. The analysis results show that the structural work has an estimated completion time of 303 days with a probability of 96.56% (z = 1.824). When compared to the actual field duration of 321 days, an 18-day delay was identified in the structural work. This delay was caused by several factors, including work complexity, long activity durations, and interdependencies among work disciplines. This study contributes to the application of the PERT method for evaluating time performance in construction projects and serves as a reference for decision-making in time planning for similar projects. Keywords— Project Performance, PERT, Time Estimation